Prenatal Nutritional Intervention Reduces Autistic-Like Behavior Rates Among Mthfr-Deficient Mice - Orenbuch, Ayelet; Fortis, Keren; Taesuwan, Siraphat; Yaffe, Raz; Caudill, Marie A.; Golan, Hava M. (Frontiers in Neuroscience, 2019)
The causes and contributing factors of autism spectrum disorders (ASD) are poorly understood. One gene associated with increased risk for ASD is methylenetetrahydrofolate-reductase (MTHFR), which encodes a key enzyme in one carbon (C1) metabolism. The MTHFR 677C>T polymorphism reduces the efficiency of methyl group production with possible adverse downstream effects on gene expression. In this study, the effects of prenatal and/or postnatal diets enriched in C1 nutrients on ASD-like behavior were evaluated in Mthfr-deficient mice. Differences in intermediate pathways between the mice with and without ASD-like behaviors were tested. The findings indicate that maternal and offspring Mthfr deficiency increased the risk for an ASD-like phenotype in the offspring. The risk of ASD-like behavior was reduced in Mthfr-deficient mice supplemented with C1 nutrients prenatally. Specifically, among offspring of Mthfr+/- dams, prenatal diet supplementation was protective against ASD-like symptomatic behavior compared to the control diet with an odds ratio of 0.18 (CI:0.035, 0.970). Changes in major C1 metabolites, \such as the ratios between betaine/choline and SAM/SAH in the cerebral-cortex, were associated with ASD-like behavior. Symptomatic mice presenting ASD-like behavior showed decreased levels of GABA pathway proteins such as GAD65/67 and VGAT and altered ratios of the glutamate receptor subunits GluR1/GluR2 in males and NR2A/NR2B in females. The altered ratios, in turn, favor receptor subunits with higher sensitivity to neuronal activity. Our study suggests that MTHFR deficiency can increase the risk of ASD-like behavior in mice and that prenatal dietary intervention focused on MTHFR genotypes can reduce the risk of ASD-like behavior.